RETRACTED: Harnessing TRAIL-Induced Apoptosis Pathway for Cancer Immunotherapy and Associated Challenges - Razeghian, Ehsan; Suksatan, Wanich; Sulaiman Rahman, Heshu; Bokov, Dmitry O.; Abdelbasset, Walid Kamal; Hassanzadeh, Ali; Marofi, Faroogh; Yazdanifar, Mahboubeh; Jarahian, Mostafa (Frontiers in Immunology, 2021)
ABSTRACT The immune cytokine tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) has attracted rapidly evolving attention as a cancer treatment modality because of its competence to selectively eliminate tumor cells without instigating toxicity in vivo. TRAIL has revealed encouraging promise in preclinical reports in animal models as a cancer treatment option; however, the foremost constraint of the TRAIL therapy is the advancement of TRAIL resistance through a myriad of mechanisms in tumor cells. Investigations have documented that improvement of the expression of anti-apoptotic proteins and survival or proliferation involved signaling pathways concurrently suppressing the expression of pro-apoptotic proteins along with down-regulation of expression of TRAILR1 and TRAILR2, also known as death receptor 4 and 5 (DR4/5) are reliable for tumor cells resistance to TRAIL. Therefore, it seems that the development of a therapeutic approach for overcoming TRAIL resistance is of paramount importance. Studies currently have shown that combined treatment with anti-tumor agents, ranging from synthetic agents to natural products, and TRAIL could result in induction of apoptosis in TRAIL-resistant cells. Also, human mesenchymal stem/stromal cells (MSCs) engineered to generate and deliver TRAIL can provide both targeted and continued delivery of this apoptosis-inducing cytokine. Similarly, nanoparticle (NPs)-based TRAIL delivery offers novel platforms to defeat barricades to TRAIL therapeutic delivery. In the current review, we will focus on underlying mechanisms contributed to inducing resistance to TRAIL in tumor cells, and also discuss recent findings concerning the therapeutic efficacy of combined treatment of TRAIL with other antitumor compounds, and also TRAIL-delivery using human MSCs and NPs to overcome tumor cells resistance to TRAIL.